2020
DOI: 10.3390/ijms22010107
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Coffee Bioactive Compounds: A Review

Abstract: Coffee is one of the most widely consumed beverages worldwide. It is usually identified as a stimulant because of a high content of caffeine. However, caffeine is not the only coffee bioactive component. The coffee beverage is in fact a mixture of a number of bioactive compounds such as polyphenols, especially chlorogenic acids (in green beans) and caffeic acid (in roasted coffee beans), alkaloids (caffeine and trigonelline), and the diterpenes (cafestol and kahweol). Extensive research shows that coffee consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 401 publications
1
107
0
3
Order By: Relevance
“…Several studies demonstrate that coffee induces beneficial effects on many human diseases, including cardiovascular, neurodegenerative and cancerous ones [1][2][3]26]. Unfortunately, due to the many roasting and brewing methods for making coffee and coffee-based beverages, the composition of bio-compounds may differ significantly [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrate that coffee induces beneficial effects on many human diseases, including cardiovascular, neurodegenerative and cancerous ones [1][2][3]26]. Unfortunately, due to the many roasting and brewing methods for making coffee and coffee-based beverages, the composition of bio-compounds may differ significantly [27].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence points to a positive correlation between habitual coffee consumption and the reduced risk of several diseases including type 2 diabetes and neurological, neurodegenerative and cardiovascular diseases [1][2][3]. In addition, several studies have shown that increased coffee consumption is associated with decreased mortality from different types of cancer including melanoma [4], colorectal [5], prostate [6], lung [7], liver [8], and breast cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeoylquinic acids have been investigated in different diseases because of its anti-oxidative, antibacterial and antiparasitic effect, anti-inflammatory activity, reduction of chronic pain, such as neuroprotective, anticancer, cardiovascular and antidiabetic effects (Scholz et al, 1994; Li et al, 2018a; Santana-Gálvez et al, 2017; Bagdas et al, 2019; Socała et al, 2021). In particular, caffeoylquinic acids were investigated for the treatment of cancer, cardiovascular disease, diabetes, cognitive impairment, hypercholesterolemia, nutritional and metabolic diseases, and impaired glucose tolerance (reviewed in Liu et al (2020)).…”
Section: Discussionmentioning
confidence: 99%
“…Caffeoylglucaric acid, the last identified PSM, is known to be synthesized in tomato from chlorogenic acid and glucaric acid by chlorogenic acid:glucaric acid caffeoyltransferase (Strack et al, 1987;Strack and Gross, 1990). It can be found in a wide variety of foods and beverages, including fruits, vegetables, olive oil, spices, wine, and especially coffee (Pérez-Jiménez et al, 2010;Socała et al, 2021), as well as tobacco leaves (Sheen, 1973). Along with chlorogenic acid (5-O-caffeoylquinic acid, also called 5-CQA), 4-O-caffeoylquinic acid (also called neochlorogenic acid) and 3-O-caffeoylquinic acid (also called cryptochlorogenic acid) appear as well in the plant kingdom (reviewed in Liu et al (2020)), while 1-Ocaffeoylquinic acid was seldom isolated (Parejo et al, 2004).…”
Section: Nitrogen Deficiency and Secondary Metabolismmentioning
confidence: 99%
“…One of the most relevant bioactive compounds with proven neuroprotective effects are contained in the coffee. Caffeine is perhaps the best-known component, although there are many other components including polyphenols, especially chlorogenic acids (in green beans) and caffeic acid (in roasted coffee beans), alkaloids (caffeine and trigonelline) and the diterpenes (cafestol and kahweol) [ 240 ]. Overall, these bioactive compounds interact together to exert their beneficial effects in the brain.…”
Section: Nutraceuticals In Mddmentioning
confidence: 99%